A modular framework for the development of peer-to-peer applications and services. (22nd August 2011) - Andreica, Mugurel Ionuţ; T∈rşa, Eliana-Dina; Ţăpuş, Nicolae
The development of peer-to-peer architectures and services is a cumbersome task, as it needs to handle multiple aspects at many levels (e.g., communication, coordination, topology construction and management, etc.). In order to facilitate the development process, several frameworks and component models have been proposed which allow the developer to focus on the main functionality of the service or application, without having to deal with the other aspects. In this paper, we propose a new modular framework for constructing and maintaining peer-to-peer overlays on top of which applications and services can be developed and deployed. We also consider two services, a multicast communication service and a data storage and retrieval service, and show how they can be developed using our framework.